Understanding level on the concept of islamic multilevel marketing among Malays at Kampung Sungai Chinchin, Gombak / Ayuni Zafirah Amir - Amir, Ayuni Zafirah (2019)
Multi-level marketing is one of the business schemes that established in Malaysia. However, there are not much citizen of Malaysia well-known about this business scheme. As the researcher have limited time to ongoing this research, the researcher decide to appoint on the understanding level among community at Kg. Sg. Chinchin, Gombak on Islamic Multi-level marketing concept. As MLM known as profitable business, it is important to encourage Malays to be one of MLM members. The encouragement is due to the percentage of poverty among Malays that have been recorded as a higher race that face this problem. As a result, the researcher decided to proceed this research as an alternative to make the percentage among Malays and other races in Malaysia decrease in a time. Hence, this research was using qualitative method by applying internet research and interview session to get as much data. Various authority website were used and selected informants were questioned during the interview in order to have accurate and reliable data. Yet, Islamic Multi-level marketing is still open for further discussion. This is because so far only JAKIM has issued guidelines to notice that the MLM Company run an Islamic Multi-level marketing business, without government enforcement with more realistic and specific laws regarding Islamic Multi-level marketing. Thus, this issue needs to be addressed with more studies to be carried out so that there will be specific laws regarding Islamic MLM someday.